A regulatory regime for financial stability - David T. Llewellyn (Oesterreichische Nationalbank (OeNB), 2001)
As bank failures clearly involve avoidable costs, there is a welfare benefit to be derived from lowering their probability and reducing the cost of those that do occur. The paper suggests a paradigm for enhanced financial stability. A central theme is that, what are often viewed as alternatives, are in fact complements within an overall regulatory strategy. The discussion is set within the context of what is termed a regulatory regime which is wider than the rules and monitoring conducted by regulatory agencies. Just as the causes of banking crises are multi-dimensional, so the principles of an effective regulatory regime also need to incorporate a wider range of issues than externally imposed rules on bank behaviour. The key components of the regime are: (1) the rules established by regulatory agencies; (2) monitoring and supervision by official agencies; (3) the incentive structures faced by regulatory agencies, consumers and banks; (4) the role of market discipline and monitoring; (5) intervention arrangements in the event of bank failures; (6) the role of internal corporate governance arrangements within banks, and (7) the disciplining and accountability arrangements applied to regulatory agencies. The central theme is that the components of the regulatory regime need to be combined in an overall regulatory strategy, and that while all are necessary, none alone are sufficient. The objective is to optimise a regulatory strategy by combining the components of the regime, bearing in mind that negative trade-offs may be encountered. Thus, if regulation is badly constructed or taken too far, there may be negative impacts on other components to the extent that the overall effect is diluted. The paper also argues that the optimum mix of the components of the regime will vary between countries, over time for all countries, and between banks. The proposed New Basel Capital Accord is discussed in terms of the regulatory regime paradigm.
Keywords: 330